Simple and scalable manufacturing of metal/carbon hybrid EMI shielding fabric across a broad frequency range - YeonJoo Lee; Jungjoon Kim; Youngkyun Kim; Hyokyung Sung; Jae Bok Seol; Kisub Cho; HwiJun Kim; Hyunjoo Choi (Journal of Materials Research and Technology, 2025)
As electromagnetic interference (EMI) shielding demands expand from 30 MHz to 3 GHz, efforts to develop metal/carbon hybrid fabrics have increased; however, the majority rely on complex chemical processes. This study introduces a commercially viable aluminum/carbon fiber (Al/CF) hybrid shielding material fabricated using a simple pressing process to overcome the limitations of conventional chemical methods. The interfacial bonding between Al and CF was optimized by adjusting the pressing temperature and pressure. Surface conductivity, bonding strength, and bending durability were evaluated to determine their sustainability as shielding fabrics. Compared to the hybrid manufactured through the chemical process (maximum 0.2 × 104 S/cm), the hybrid manufactured through the mechanical process (20 × 104 S/cm) showed approximately 100 times higher conductivity at the highest temperature and pressure conditions of 600 °C and 280 MPa and maintained the highest conductivity (20 × 104 S/cm) even after 16 cycles of bending tests. This is because the hybrid material manufactured in this study exhibited uniform and excellent bonding properties owing to a mechanical rather than chemical process. The results of this study are expected to contribute to the development of hybrid materials with excellent electromagnetic shielding properties for efficient and widespread applications in advanced industrial fields.